2017
DOI: 10.1186/s13063-017-2190-2
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of two web-based cognitive bias modification interventions targeting approach and attentional bias in gambling problems: study protocol for a pilot randomised controlled trial

Abstract: BackgroundDisordered gamblers have phenotypical and pathological similarities to those with substance use disorders (SUD), including exaggerated automatic cognitive processing of motivationally salient gambling cues in the environment (i.e., attentional and approach bias). Cognitive bias modification (CBM) is a family of computerised interventions that have proved effective in successfully re-training these automatic cognitive biases in SUD. CBM interventions can, in principle, be administered online, thus sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 73 publications
(94 reference statements)
1
18
0
Order By: Relevance
“…Specific adjuvant interventions to address the facets of impulsivity associated with GD severity could potentially improve treatment outcomes 4,5 . In this sense, technologically based interventions represent a new frontier for treatment, from the computerized adaptation of neurocognitive tasks to evaluate these processes, such as cognitive and attentional bias 81 , to the use of mobile applications to condition the selection of healthy foods obesity 82 , or serious games for the treatment of impulsivity in gambling disorder 83 , in eating disorders 84,85 and in other mental disorders 86 . It has been observed that the use of therapeutic video games, as an additional therapeutic tool can treat difficulties in emotional regulation and impulsivity 84 .…”
Section: Discussionmentioning
confidence: 99%
“…Specific adjuvant interventions to address the facets of impulsivity associated with GD severity could potentially improve treatment outcomes 4,5 . In this sense, technologically based interventions represent a new frontier for treatment, from the computerized adaptation of neurocognitive tasks to evaluate these processes, such as cognitive and attentional bias 81 , to the use of mobile applications to condition the selection of healthy foods obesity 82 , or serious games for the treatment of impulsivity in gambling disorder 83 , in eating disorders 84,85 and in other mental disorders 86 . It has been observed that the use of therapeutic video games, as an additional therapeutic tool can treat difficulties in emotional regulation and impulsivity 84 .…”
Section: Discussionmentioning
confidence: 99%
“…As a strong approach bias towards gambling increases the likelihood of persisting in gambling, which implies the risk of ultimately exacerbating gambling problems, it is reasonable to propose that neurocognitive interventions targeting these dysfunctional implicit motivational processes, e.g. re‐training selective attention and approach bias via cognitive bias modification (CBM) , may reduce the risk of problem gambling escalation and/or relapse . By reducing effectively the coding of salient cues in the brain reward system , CBM training programmes have the potential of re‐wiring action‐value representations associated with appetitive gambling cues, particularly when using gambling stimuli tailored to the individual's most familiar and frequently played gambling activities.…”
Section: Resultsmentioning
confidence: 99%
“…A key‐press version of the AAT was used to assess online gambling approach bias . Participants were instructed to approach (‘pull’) or avoid (‘push’) gambling‐related and neutral pictures by responding as quickly and accurately as possible to the rotation direction (5 degrees) of the pictures with two keys on the keyboard (see the Supporting information for a detailed description of the task).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations